Implementasi Metode Bernyanyi dalam Meningkatkan Kosa Kata Bahasa Arab TK Alam Surya Mentari Muhamadiyah Surakarta: Penelitian - Putri Ristika Ayuni; Maslamah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Arabic language learning is one of the subjects that can be taught to early childhood students. One of the methods used to teach Arabic to young children is the singing method, which helps them memorize Arabic vocabulary more easily. The purpose of this study is to examine the implementation of the singing method in enhancing and facilitating children's ability to memorize vocabulary (mufrodat).This study employs a qualitative research approach, utilizing observation techniques to analyze the learning process involving kindergarten students at TK Alam Surya Mentari Surakarta as the research subjects. The data analysis technique consists of three stages: data processing, data analysis, and interpretation of the results.The findings indicate that children tend to prefer the singing method in learning Arabic, as it helps them memorize vocabulary more effectively. During the learning process, teachers introduce various themes such as colors, numbers, and objects. Additionally, teachers incorporate posters or images when introducing vocabulary to children. This approach is considered effective in enhancing children's understanding and interest in learning Arabic.